Intravenous Dexamethasone as Prophylaxis Against Laryngeal Edema Associated with Changes in Sound Quality in Patients Undergoing Total Thyroidectomy - Eduardus Gilang Putra; Maman Abdurahman; Kiki Ahmad Rizki (Majalah Kedokteran Bandung, 2022)
Thyroidectomy is a relatively safe surgical procedure for thyroid gland removal with a with mortality and morbidity rates of less than 2–3%. Complication in the form of sound changes often goes unnoticed in post-thyroid patients despite its high incidence rate, i.e., 87% of all surgical cases. Laryngeal edema as the underlying cause can be triggered by intubation or extubation during anesthesia; malfunction of the strap muscles; surgery that directly causes injury to the superior laryngeal nerve; and recurrent laryngeal nerve injuries. Several studies on the use of dexamethasone to prevent or reduce laryngeal edema that occurs after thyroidectomy have been conducted with controversial results. This study was conducted to solve this controversy. This was a double-blind randomized prospective study on thyroid tumors patients who underwent thyroidectomy at Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from December 2020 to May 2021. This study evaluated dexamethasone effects on the patient’s sound changes using the Sound Handicap Index (VHI) questionnaire before surgery, day 1 after the surgery, and day 7 after the surgery. Analysis showed that the VHI significantly decreased on day 1 (p<0.01) and on day 7 (p<0.01), and the difference between the VHI on day 1 (D-1) and day 7 (D-7) was significant (p<0.01). When analyzed using the bivariate analysis, no statistically significant difference was found between the VHI variable before surgery, D-1, and D-7and VHI H7 in the group of patients using dexamethasone and without dexamethasone. Dexamethasone administration has no significant effect on laryngeal edema associated with changes in sound quality.